1998
DOI: 10.2118/52397-pa
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Sandstone-Acidizing Designs With Improved Radial Models

Abstract: This paper (SPE 52397) was revised for publication from paper SPE 38597, first presented at the 1997 SPE Annual Technical Conference and Exhibition held in San Antonio, Texas, 5-8 October. Original manuscript received for review 17 October 1997. Revised manuscript received 8 July 1998. Revised manuscript approved 5 August 1998. Summary With the intent of encouraging and helping the reader to design a radial model tailored to a particular use, this paper discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Among these problems are: decomposition of clays in HCl acids, the presence of carbonate can cause the precipitation of calcium fluorides (CaF 2 ), HCl-sensitive clays (eg., illite) can cause formation damage, the high reaction rate and corrosion rate at high bottomhole temperatures (Shuchart and Gdanski 1996;Thomas et al 2001), and mixing between various stages of the treatment may occur during the treatment by mud acid (Gdanski and Shuchart 1998).…”
Section: Problem Associated With Mud Acid Treatmentsmentioning
confidence: 99%
“…Among these problems are: decomposition of clays in HCl acids, the presence of carbonate can cause the precipitation of calcium fluorides (CaF 2 ), HCl-sensitive clays (eg., illite) can cause formation damage, the high reaction rate and corrosion rate at high bottomhole temperatures (Shuchart and Gdanski 1996;Thomas et al 2001), and mixing between various stages of the treatment may occur during the treatment by mud acid (Gdanski and Shuchart 1998).…”
Section: Problem Associated With Mud Acid Treatmentsmentioning
confidence: 99%
“…The CIR scale developed for acidizing was based on the rate of acid attack on clays, which released aluminum into solution and caused amorphous silica gel to form. 7 The rate of attack was determined by adjusting the value of the rate constant in the rate law for that attack. This same approach was used to develop the high-pH CIR scale.…”
Section: → +mentioning
confidence: 99%
“…6 Even with these developments, the powerful effect of ion exchange transformation of brines used for stimulation and remedial workovers escaped broad notice until recently. 7,8 In a similar fashion, the powerful effect of clay acidity has only slowly been brought into proper awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Gdanski and Scuchart (1998) have shown that essentially all clays are unstable in HCl above 300 o F. The ideal stimulation fluid would remove the near-wellbore damage without depositing precipitates in the formation, and preventing well production declines due to solids movements. Martin (2004) has showed that it was possible to stimulate sandstone formation without subsequent need for HF acid.…”
Section: Introductionmentioning
confidence: 99%